Efficacy and safety of lenalinomide combined with rituximab in patients with relapsed/refractory diffuse large B-cell lymphoma. Issue 11 (November 2014) - Ivanov, Vadim; Coso, Diane; Chetaille, Bruno; Esterni, Benjamin; Olive, Daniel; Aurran-Schleinitz, Therese; Schiano, Jean Marc; Stoppa, Anne-Marie; Broussais-Guillaumot, Florence; Blaise, Didier; Bouabdallah, Reda
Abstract: Initial clinical trials demonstrated that lenalidomide monotherapy has a significant activity against some subtypes of lymphoma, but in diffuse large B-cell lymphoma (DLBCL) its activity is limited. The combination of lenalidomide with rituximab may be a promising therapeutic strategy. We retrospectively analyzed clinical outcomes in 17 patients with relapsed/refractory (R/R) DLBCL treated with lenalidomide, 25 mg/day for 21/28 days and rituximab, 375 mg/m 2 on day 7 of every lenalidomide cycle, for a maximum of 12 months. The overall response rate (ORR) was 41.2% with 35.3% complete response (CR), while median response duration was 26.5 months at a median follow-up of 24.9 months. Two patients with CR relapsed after 4 and 27 months of CR, and another four are actually in CR at + 13, + 23, + 24 and + 29 months. The estimated 24-month overall survival (OS) was 45% and progression-free survival (PFS) was 38%. Adverse events were manageable and mostly included thrombocytopenia and neutropenia. Lenalidomide–rituximab is active in R/R DLBCL with an important percentage of continuous CR.